Fifty percent human - how art brings us in touch with our microbial cohabitants - Bäumel, Sonja; Tytgat, Hanne L. P.; Nemec, Birgit; Schmidt, Ruth; Chia, Loo Wee; Smidt, Hauke (Microbial biotechnology, 2018)
The Human Microbiome, as well as the exploration of the microorganisms inhabiting the human body, are not only integral to the field of microbiology but represent an intrinsic part of all human beings. Consequently, along with scientists, artists have been inspired by the microbiome: transforming it in to tangible artefacts in order to critically question, reflect on and break down the barrier between humans and their microcohabitants. By artistic means, artists help us to understand how microbial research topics are inevitably affected by societal influences, including (health) politics, economics and the arts. Fifty Percent Human is a multidisciplinary artistic research project that aims to reshape our understanding of the human body and its environment as well as to explore possibilities for conscious coexistence in order to bridge the gap between science and society.